CHARACTER ASSOCIATION AND PATH ANALYSIS IN RICE (ORYZA SATIVA L.) - PANWAR, L.L. (Annals of Agricultural Research, 2014)
Thirty F1 hybrids and thirteen parents were studied for estimating the genotypic and phenotypic correlation coefficients and path effects of yield attributing traits on grain plant-1. Grain yield plant-1 had significant positive association with harvest index, grain yield panicle-1, filled grain yield panicle-1, productive tillers plant-1, harvest index and filled grains panicle-1 were the major yield contributing traits to be given selection pressure for improving yield in rice.